Findings of Ecomapa and APGAR practice of Nursing to the Family in two sectors of Pereira, 2022 - Lina Marcela Suárez Gaviria; Luz Enith Velásquez Restrepo; Blanca Doris León Mejía (International Journal of Medical Toxicology and Legal Medicine, 2023)
Introduction: the APGAR and the ecomap allow a global evaluation of the degree of coping or overcoming crises and the interactions with the open system that is the family with other resources. Objective: to characterize sociodemographically the families and to describe the findings in the implementation of the APGAR and ecomap assessment tools during the Family Nursing practice. Methodology: Descriptive study, with quantitative approach, convenience sample, 38 families of socioeconomic stratum I and II were taken as population, resulting from the visits made by students of IV Semester of Nursing, with prior informed consent. A characterization instrument was used to collect data, which was reviewed and endorsed by experts. Results: the main cause of migration is the armed conflict, since most of the families are displaced from the departments of Risaralda and Chocó; most of the population has their own home and is between 15 and 49 years old; the highest educational level is technical; most of the families are of complete nuclear typology, according to the ecomap, the resources with the highest percentage of strong interaction were: public services, health, housing and work, as well as "High Family Functionality", according to the APGAR. Conclusions: family characterization is a technique that allows the identification of strengths in those families that are socially vulnerable, the findings in the implementation of family assessment tools (APGAR and Ecomapa), demonstrated its importance for the training practices of future nursing professionals.